Методологічні проблеми оцінки ефективності мотивації конкурентоспроможності у сфері праці - Онікієнко, В.В.; Семикіна, М.В. (Інститут демографії та соціальних досліджень НАН України, 2006)
В статье исследуются методологические проблемы оценки мотивации конкурентоспособности в сфере труда. Предложено новое научное направление, базирующееся на концепции мотивации конкурентоспособного труда. Разработана система показателей экономической и социальной эффективности мотивации труда. The article is devoted to the research of methodological problem of estimate of motivation of competitiveness in the sphere of labour. A new scientific direction which is based on the conception of motivation of competitive labour is suggested. A system of indications of economic and social effectiveness of labour motivation has been worked out.